Improving Student’s Arabic Achievement by Implementing Extracurricular Program Management - Muhammad Fadhlan; Mochammad Firdaus; Ahmad Fikri (AL-ISHLAH: Jurnal Pendidikan, 2024)
The lack of support for language activities outside the classroom leads to failure in learning Arabic. This research aims to address this issue through three main objectives: first, to design extracurricular management for improving students' Arabic language skills; second, to explain the processes of organizing, implementing, and evaluating the Arabic extracurricular program; and third, to assess students' success after participating in the program. Employing a qualitative case study approach, data were collected through observation and in-depth interviews with six extracurricular teachers across four Arabic extracurricular classes, including news reading, speech, and scientific debate. Semi-structured interviews in Indonesian facilitated easier responses and minimized language barriers for participants. Thematic analysis of the data revealed that students' achievement in Arabic can be significantly enhanced through well-designed extracurricular activities. Key factors include selecting appropriate activities, appointing effective supervisors, aligning student interests with their talents, and implementing innovative strategies with relevant material. Additionally, conducting weekly and semester evaluations is crucial for monitoring and improving student learning outcomes in Arabic.